(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
In this interview, carried out during the International Seminar on Theatrical Pedagogies and Indigenous Peoples: decolonizing the formation of the artist-teacher-research person, the graduate in Theater from the State University of Southwest Bahia (UESB), Eliana Silva Santos Pataxó and the graduate in Theater from Federal University of Tocantins (UFT), Edmar Srenokra Xerente, alongside the supervisors of their Course Completion Works, Maria Aparecida de Souza (UESB) and Karylleila Andrade (UFT) comment on the experiences in their communities, the difficulties to enter and remain in the university, the relationships with the curricula and subjects of the courses, the artistic and pedagogical interventions carried out during the graduation period and at the end, the return to the community and the continuity of the studies. In May 2021, given the health crisis caused by the new coronavirus (COVID-19), the interview was conducted through a video call.